Metabolite Signature of Fresh and Long-term Stored Coffee Pulp and Husk - Lestari, Wahyu; Hasballah, Kartini; Listiawan, Muhammad Yulianto; Sofia, Sofia (UI Scholars Hub, 2022)
Every product from the food and agriculture industry produces waste that can cause environmental pollution when carelessly discarded. Coffee husk and pulp are the main wastes generated by coffee processing. The secondary metabolites in these wastes can still be utilized, but their level can be affected by long storage. This research aims to determine the differences in the compounds obtained from old and fresh Gayo Arabica coffee pulp and husk. Coffee husk and pulp samples from Gayo Arabica coffee are extracted for GC-MS analysis to determine similarities between fresh and long-term stored Gayo Arabica coffee husk and pulp. Results show differences in level and type among the secondary metabolites. Among various compounds, caffeine is found in all the samples. The compounds obtained from Gayo Arabica coffee husk and pulp, such as caffeine, (Z,Z)-9,12-octadecadienoic acid, and palmitic acid, can be used in health and agriculture.